Особливостi детектування вiдновлювальних газiв сенсорами на основi In2O3 i SnO2 у вологiй атмосферi - Golovanova, V. V.; Nazarchuk, B. V.; Semenov, A. K.; Postnyi, A. V.; Golovanov, V. V. (Publishing house "Academperiodika", 2018)
Interaction of SnO2- and In2O3-based sensors with the reducing CO and CH4 gases in a humid atmosphere has been studied. The atmospheric moisture is shown to have a significant influence on the sensor conductivity, as well as on the correlation between the sensor sensitivity and catalytic activity. The results obtained are analogous for various oxides and reducing gases. The mechanism of interaction of a reducing gas with the oxide surface in the humid environment is proposed. Using the calculations carried out in the framework of the density functional theory, two different types of hydroxyl radicals on the oxide surface are identified. They differently affect the conductivity and sensitivity of the sensor at its interaction with reducing gases. The proposed model is experimentally confirmed by joint measurements of the sensitivity and catalytic activity of studied oxides.